2009
DOI: 10.1002/elan.200904579
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalysis of Norepinephrine at Bare Gold Electrode Pure and Modified with Gold Nanoparticles and S‐Functionalized Self‐Assembled Layers in Aqueous Solution

Abstract: Gold nanoparticles (Au-NPs), cystamine (CA) and 3,3'-dithiodipropionic acid (DTDPA) modified gold bare electrodes were applied in voltammetric sensors for simultaneous detection of norepinephrine (NEP), ascorbic (AA) and uric (UA) acids. A linear relationship between norepinephrine concentration and current response was obtained in the range of 0.1 mM to 600 mM M with the detection limit 0.091 mM for the electrodes modified at 2D template and in the range of 0.1 mM to 700 mM M with the detection limit 0.087 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 53 publications
3
19
0
Order By: Relevance
“…This is in agreement with literature data, as it has been shown that the Au nanoparticles of diameters between 2.6 nm and 20 nm could be expected when the absorption maximum appears between 514 nm and 530 nm, respectively [33,34]. The diameter of the Au-NPs particles used in this study was the same as that reported in the earlier studies [22,33,35] when the same procedure of Au colloidal solution preparation as in the present paper was used.…”
Section: Ausupporting
confidence: 92%
See 3 more Smart Citations
“…This is in agreement with literature data, as it has been shown that the Au nanoparticles of diameters between 2.6 nm and 20 nm could be expected when the absorption maximum appears between 514 nm and 530 nm, respectively [33,34]. The diameter of the Au-NPs particles used in this study was the same as that reported in the earlier studies [22,33,35] when the same procedure of Au colloidal solution preparation as in the present paper was used.…”
Section: Ausupporting
confidence: 92%
“…Au=Au À NPs : ðAu The electrodes treatment after modification and electrochemical experiments as well as the way of electrodes storage were the same as described earlier [22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown, the colloidal gold gives the maximum absorbance at about 520 nm. This length was the same as that obtained earlier [29,30,33,34]. It is known that the Au nanoparticles of diameters between 2.6 nm and 20 nm could be expected when the absorption maximum appears between 514 nm and 530 nm.…”
Section: Resultsmentioning
confidence: 56%